Fungsi Institusi Pendidikan dalam Upaya Sosialisasi Pencegahan Kekerasan Seksual dan Pelecehan Seksual pada Anak (Neolectura, 2023)
Sexual violence and child abuse have become serious and widespread issues in school and adolescent environments. This phenomenon has physical, psychological, sexual, and social impacts on the victims. Involvement of the government, society, and educational institutions, as well as legal efforts and socialization, is crucial in preventing and addressing this issue. The main objective of this community service is to provide awareness about protection and create a sense of security for children, while also striving to enhance the role of families through socialization conducted by educational institutions. The method employed in this event is through face-to-face socialization by introducing the basic legal concepts used by the government to prohibit